Effect of Bruton's tyrosine kinase inhibitors on platelet aggregation in patients with acute myocardial infarction. Issue 179 (July 2019) - Bhatti, Maria; Ayton, Sarah; Michail, Olga; Gollop, Nicholas D.; Ryding, Alisdair; Rushworth, Stuart; Bowles, Kristian; Geisler, Tobias; Flather, Marcus
Abstract: Aims: Despite widespread use of dual antiplatelet therapy in acute myocardial infarction, there remains a residual risk of morbidity and mortality. Bruton's Tyrosine Kinase inhibitors have been found to inhibit platelet aggregation through the Glycoprotein VI collagen-mediated pathway. The Bruton's Tyrosine Kinase inhibitor, Ibrutinib is used in the management of haematological malignancies and another Bruton's Tyrosine Kinase inhibitor, ONO-4059 (also known as tirabrutinib), is in clinical development. This is an observational study to evaluate the effects of Ibrutinib and ONO-4059 on platelet aggregation after acute myocardial infarction. Methods and results: Twenty patients with a confirmed diagnosis of acute myocardial infarction were enrolled and blood samples obtained within 48 h of hospital admission. All patients were on dual antiplatelet therapy; aspirin plus a P2Y12 inhibitor (clopidogrel or ticagrelor). Blood samples were treated ex vivo with increasing concentrations of Ibrutinib (0, 0.5, 1, 2 μM) and ONO-4059 (0, 0.2, 0.5, 1 μM). Platelet aggregation was measured in response to collagen using a Multiplate analyser to estimate the area under the curve, with lower values indicating lower platelet aggregation. The median age was 63 years and 80% were male. The median area under the curve values for Ibrutinib concentrations 0 (control), 0.5, 1 and 2 μM were 18.5, 8 (P = 0.0004), 4.5 (P < 0.0001) and 2 (P < 0.0001) units and for ONO-4059 concentrations 0 (control), 0.2, 0.5 and1μM, median area under the curve values were 13, 12 (P = 0.7), 6.5 (P = 0.0001) and 5.5 (P = 0.0004 compared to control). Conclusion: The Bruton's Tyrosine Kinase inhibitors, Ibrutinib and ONO-4059, show further inhibition of platelet aggregation in blood samples from patients with acute myocardial infarction, receiving dual antiplatelet therapy in a dose dependent manner. These results provide a rationale for Bruton's Tyrosine Kinase inhibitors to be tested as a potential new antiplatelet strategy for acute myocardial infarction. Highlights: Bruton's tyrosine kinase inhibitors affect the glycoprotein VI collagen pathway. They add further platelet inhibition in blood samples after myocardial infarction. This provides a rationale for clinical testing as potential new antiplatelet agents.